Home health care - Elias, Jaan; Blumenthal, Adam; Rosenthal, Jean; Kogler, Jeremy (London : Yale School of Management, 2020)
Blue Wolf Capital Partners was making major investments in the home health care sector. The private equity fund had purchased two U.S. regional companies in the space - NHHC (National Home Health Care Corporation), announced in November 2015, and GLC (Great Lakes Caring Home Health and Hospice), announced in May 2016, with an investment reported as $104 million. The plan was to merge the two organizations, creating opportunities for shared expertise and synergies in reducing management costs.
Originally Published InElias, J., Blumenthal, A., Rosenthal, J., & Kogler, J. (2020). Home Health Care. 20-012. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Consolidation and merger of corporations -- Case studies; Home care services -- Mergers -- Case studies; Investments -- Case studies